The Effectiveness of Blended Learning For Undergraduate Nursing Students: A Systematic Review - Tarigan, Yohanes Zenriano; Kusumaningtyas, Dwi Prima Hanis; Simanjuntak, Therecia (Babali Publisher, 2025)
Introduction: Implementing conventional and online learning is considered insufficient to balance current educational needs, so blended learning is needed, combining the two learning methods to include more comprehensive learning. This study aims to systematically investigate the literature regarding the effectiveness of blended learning for undergraduate nursing students in Indonesia. Methods: Systematic review by searching articles using CINAHL, PubMed, Science Direct, ProQuest, SINTA, GARUDA, manual search, and electronic search engine